The decision support system in the performance appraisal of employees by applying the method of Simple Additive Weighting (SAW) - Cahyani Budihartanti; T. Tuslaela; D. Desmira (VOLT : Jurnal Ilmiah Pendidikan Teknik Elektro, 2019)
The success or success of a company cannot be separated from the performance of employees in the company. To make a company successful, competent employees are needed. The Human Re-sources (HR) section is assigned to look for competent employees. Many ways are done by the HR department to obtain or produce competent employees, namely by evaluating employee perfor-mance. Performance appraisal is also a tool for superiors, especially HR in making decisions relat-ed to promotion promotion. Currently the performance appraisal is done by filling out the employ-ee performance form and then the data is processed using the Excel application. The more data that is processed, the greater the level of error in evaluating employee performance. Therefore, to reduce the error rate and produce more accurate data, an information system application that applies the Simple Additive Weighting (SAW) method is applied. The SAW method which is com-bined with the application of fuzzy logic in giving weight to each assessment criterion is one of the appropriate methods in evaluating employee performance. The stages of the SAW method are by setting criteria and then determining the weight of each criterion, the next step is to determine the suitability rating that will produce a decision matrix. From the decision matrix will be calculated matrix normalization based on equations that have been adjusted to the type of benefit attributes so that the normalized matrix R is obtained, the last stage of the SAW method is a ranking process that will determine employees in promotion promotion. Based on the results of calculations using the SAW method, the results of employees with the name Diva Amelia get the highest rank and are entitled to get awards for their performance.